THE MEXICAN FRANKLINIELLA AUREA MOULTON, F. BISAETAEVENUSTA SP. NOV., AND F. PROTHORACIGLABRA SP. NOV. SPECIES ASSEMBLAGES IN THE "INTONSA GROUP" (INSECTA, THYSANOPTERA: THRIPIDAE) - Johansen, Roberto M.; Mojica Guzmán, Aurea (Instituto de Ecología, A.C., 2003)
A review of the North American (Mexico and the United States of America) species Frankliniella aurea Moulton, 1948, was carry out herein. It is now recognized as a "species complex", since its adults show three color forms; new data about the adults of both sexes is included, together with the description of the male. Three new related species, two from North Eastern Mexico, and one from North Western Mexico were described, allowing the integration of a "species assemblage", that also includes the Brazilian species F. zucchini Nakahara and Monteiro, 1999 which was recently found in Mexico; in the study of these species, the absence of the postocular setae i was pointed out. Futhermore, there are also included two related "species assemblages", F. bisaetaevenusta sp. nov. and F. prothoraciglabra sp. nov. each with three new Mexican species. It was concluded that the Frankliniella aurea Moulton species assemblage, is related to the F. occidentalis (Pergande) species assemblage; the F. bisaetaevenusta species assemblage is related to the F. williamsi Hood species assemblage, whereas the F. prothoraciglabra species assemblage is related to the F. ipomoeae Watson species assemblage. Pertinent data about the agroecosystems and natural ecosystems, as well as geographic distribution was discussed. Illustrations of the head, antennae, thorax and abdomen of 10 examined species are included.